Analisis penggunaan media interaktif wordwall terhadap pengaruh belajar pada mata pelajaran ipa di tingkat sekolah dasar - Sri Mulyasari; Banun Havifah Cahyo Khositono; Elyas Djufri (Indonesian Journal of Learning and Educational Studies, 2026)
Learning science presents challenges, particularly in helping students understand concepts related to changes in the form of objects and maintaining their learning motivation. To address this, interactive game-based learning media like Wordwall can be utilized. This study aimed to analyze the effect of interactive Wordwall media on students’ learning outcomes in Natural Science (IPA) at the elementary school level. The research employed a quantitative approach with a quasi-experimental design involving two groups of Grade III students: an experimental class using Wordwall and a control class receiving conventional instruction. Data were collected through tests, questionnaires, and observations, then analyzed using paired and independent sample t-tests with SPSS. The results showed that the average pre-test scores of the control and experimental classes were 69.50 and 69.85, respectively, while the post-test scores increased to 76.80 and 83.85. These findings indicate that students taught using Wordwall achieved significantly better learning outcomes than those taught through conventional methods. In addition, the use of Wordwall positively influenced students’ learning motivation and participation during the learning process, as reflected in their increased engagement and active involvement in classroom activities. Therefore, interactive Wordwall media is effective in improving both students’ conceptual understanding and learning motivation in elementary science education Pembelajaran sains (IPA) di tingkat sekolah dasar memiliki tantangan tersendiri, khususnya dalam membantu siswa memahami konsep perubahan wujud benda serta menjaga motivasi belajar mereka. Untuk mengatasi hambatan tersebut, penggunaan media pembelajaran interaktif berbasis gim seperti Wordwall dapat menjadi solusi yang efektif. Penelitian kuantitatif dengan desain kuasi-eksperimen ini bertujuan untuk menganalisis pengaruh penggunaan media interaktif Wordwall terhadap hasil belajar IPA siswa kelas III SD. Data penelitian dikumpulkan melalui pre-test, post-test, kuesioner motivasi belajar, serta lembar observasi, yang kemudian dianalisis menggunakan uji-t sampel berpasangan (paired sample t-test) dan uji-t sampel independen (independent sample t-test) melalui program SPSS. Hasil penelitian menunjukkan bahwa rata-rata nilai pre-test kelas kontrol dan eksperimen adalah sebesar 69,50 dan 69,85. Setelah diberikan perlakuan, nilai rata-rata post-test meningkat signifikan menjadi 76,80 pada kelas kontrol dan 83,85 pada kelas eksperimen. Temuan ini membuktikan bahwa siswa yang belajar menggunakan media Wordwall mencapai hasil belajar yang jauh lebih baik dibandingkan dengan metode konvensional. Selain itu, pemanfaatan Wordwall terbukti berdampak positif dalam meningkatkan motivasi dan keterlibatan aktif siswa secara langsung selama proses pembelajaran di kelas. Dengan demikian, media interaktif Wordwall sangat efektif untuk meningkatkan pemahaman konsep sekaligus motivasi belajar sains anak.